Donor-π-Acceptor-π-Donor class of 2, 5-dibenzylidenecyclopentan-1-one analogues as efficient third order nonlinear optical and photoluminescent materials – An experimental investigation. (September 2019) - Harshitha, K.R.; Sarojini, B.K.; Narayana, B.; Maidur, Shivaraj R.; Patil, Parutagouda Shankaragouda; Kumara, K.
Highlights: The NLO (THG) property in D-π-A-π-D type of substituted bischalcones is determined. The HOMO-LUMO analysis and Tauc's plot complemented polarization of the analogues. The molecular architecture largely influenced photoluminescence activity. Abstract: In the present work, nonlinear optical (NLO) and optoelectronic investigations of four 2, 5-dibenzylidenecyclopentan-1-one (bischalcone) analogues 1 (4-F), 2( 4-Cl), 3 (4-Br) and 4 (3-NO2 ) with push-pull substituents (Donor-π-Acceptor-π-Donor) are studied. The third-order nonlinear optical measurements of bischalcone analogues carried out by Z-scan technique, which revealed that these compounds possess strong third-order nonlinear absorption (NLA), negative nonlinear refraction (NLR) and optical limiting behaviour under the illumination at 532 nm continuous wave laser beam (200 mW). The magnitude of third order NLA coefficient β, NLR index n2, and effective susceptibility χ (3) are found to be in the order of 10 −5 cm/W, 10 −12 cm 2 /W, and 10 −7 e.s.u respectively. The β value varied with substitution at the phenyl ring which contributed immensely on the variation. Even though the deactivating effect of 4-F, 4-Cl, 4-Br and 3-NO2 groups contributed on polarization, the presence of electron rich cyclopentanone ring ameliorated the effect of deactivation. Hence these molecules are found to possess moderate NLA and NLR properties. In addition, photoluminescence activity of these flourophores(1 –4 ) is observed as emission spectra in the range of 307–554 nm on shining at 279 nm with relative quantum yield of 1.81%, 3.8%, 1.62% and 0.89% respectively with reference to tryptophan. The HOMO-LUMO analysis for optical band gap ranged between 2.89 eV and 3.13 eV indicating polarizing nature varied with substituents.